Loke zupa decoction attenuates bronchial EMT-mediated airway remodelling in chronic asthma through the PI3K-Akt/HIF-1α signaling pathway - Jiani Liu; Li Li; Xue Han; Yue Chen; Juanjuan Diao (Taylor & Francis Group, 2023)
AbstractContext Loke zupa decoction (Lok) is a well-established classic Chinese folk remedy for asthma.Objective We sought to investigate the effect and mechanism of Lok on asthma airway remodelling and provide novel insights for the prevention and treatment of asthma.Materials and methods For in vitro experiments, BEAS-2B cells were assigned into six groups: Control, TGF-β1 (10 μM), TGF-β1 + Lok-20, TGF-β1 + Lok-40, TGF-β1 + Lok-80 μg/mL and TGF-β1 + SB431542 (5 μM). CCK8 and wound healing assays were performed. For in vivo experiments, 60 female BALB/c mice were randomly divided into 5 groups: Control, model, Lok-4.55, Lok-9.1, and DEX group. Lok was administrated by gavage during the challenge stage for 8 consecutive weeks (4.55 and 9.1 g/kg/day). We investigated airway inflammation and airway remodelling in the lungs and verified the activation status of EMT-related markers and the PI3K-Akt/HIF-1α signalling pathway.Results In vitro, Lok efficiently inhibited TGF-β1-induced BEAS-2B cell proliferation ability (cell viability 165% vs. 105%) and migration (migration areas 85% vs. 35%) without affecting their normal growth (IC50 274.2 µg/mL at 48 h). In vivo, Lok effectively protected mice from asthma, as evidenced by decreased histological damage and level of cytokines in BALF (IL-4, IL-13 and TGF-β1) by 17%-77%. Mechanistic research revealed that Lok reduced the levels of EMT-related molecules and significantly downregulated the PI3K-Akt/HIF-1α signalling pathway.Discussion and conclusions Our findings provide novel insights into the protective effect of Lok on asthma and the underlying mechanisms, providing a theoretical basis and potential treatment possibilities for this patient population.